Evaluación del proceso de generación y diseño de propuesta para el manejo de residuos peligrosos en la Subdirección del Laboratorio Aduanero de la Dirección de Impuestos y Aduanas Nacionales - U.A.E DIAN (2024)
Within the internship carried out in the Subdirectorate of the Customs Laboratory of the U.A.E DIAN, an action plan was developed with the objective of reducing hazardous waste of hydrochloric acid contaminated with metallic traces, through the procedure for determining micronutrients through curves. calibration prepared with multielement solutions, which were generated in the physicochemical analysis of atomic absorption spectrometry by flame atomization. Subsequently, the ion exchange process was defined as an alternative to purify hydrochloric acid, with the aim of using it again in washing laboratory material to clean any metallic traces that may have remained in it.